Risk factors for development of transient tachypnea of newborn - ميهوب, مها; عدنان ديوب (Latakia University Journal -Medical Sciences Series, 2022)
Background: Transient tachypnea of the newborn (TTN) is one of the most important acute respiratory diseases in the newborn period caused by delay in absorption of fetal lung liquid. Objectives: The aim of this study was to describe risk factors for development of transient tachypnea of newborn. Methods: This is a case -control study of 70 infants were diagnosed with TTN during a period from the 1st of august 2020 to the 1st of august 2021 in the neonatal intensive care unit at Tishreen University Hospital in Lattakia . 70 healthy babies born in the same period were selected as a group control. SPSS software was used for data analysis, P value <0,05 was considered as statistically significant. Results: the development of TTN was significantly associated with elective cesarean section 68,6% (p-value=0.0001), male sex 70% (p- value=0.002), maternal diabetes 7,1% (P-value=0.01),birth asphyxia (low APGAR score at 5 min) 57,1% (p-value=0.02).Tachypnea durations were longer with high respiratory rates and applied antibiotic. Conclusion: The most important risk factors for the development of TTN were elective cesarean section ,maternal diabetes, male sex, birth asphyxia (low APGAR score)